Hepatocyte growth factor and epidermal growth factor activity during later stages of rat liver regeneration upon interferon α-2b influence - Adamek, Brygida; Zalewska-Ziob, Marzena; Strzelczyk, Joanna K.; Kasperczyk, Janusz; Wołkowska-Pokrywa, Kinga; Spausta, Grażyna; Hudziec, Edyta; Wiczkowski, Andrzej; Świętochowska, Elżbieta; Kukla, Michał; Ostrowska, Zofia (Clinical and Experimental Hepatology, 2017)
Introduction : Liver regeneration is a complex, highly coordinated process which can be disturbed by the impact of the anti-proliferative interferon α activity. In the model of partial hepatectomy (PH) in the rat the expression of HGF and EGF genes and their molecules’ tissue concentrations were analyzed in the later stages of liver regeneration (48-120 h). Material and methods : 40 three-month-old male Wistar rats were randomized to groups of 20 animals each. The rats of the study group (IFN/H) were injected subcutaneously with IFNα-2b, while the control group was injected with 0.5 ml of 0.9% NaCl (NaCl/H). In the liver tissue samples obtained during hepatectomy and autopsy (regenerating liver mass) the expression of HGF and EGF genes was estimated with the Q-PCR method and the analysis of HGF and EGF molecule concentrations in tissue homogenates was conducted with the ELISA method. Results: HGF but not EGF expression was significantly higher at 48 h after PH, while EGF expression was higher in normal than in regenerating liver tissue at 120 h. The analyses of correlations between expression of HGF and EGF in regenerating liver tissue, both normal and upon IFNα-2b influence, together with correlations between those factors genes’ expression and HGF and EGF tissue concentrations in analyzed samples, showed no significant differences. Conclusions : HGF and EGF are not significantly involved in regulation of later stages of rat liver regeneration. IFNα-2b does not impact expression of their genes or the presence of these growth factor molecules in regenerating liver tissue.